National hardwoods programme: report of the eighth meeting and second meeting of the Uneven-aged Silviculture Group 7 January 1988 - Savill, P (Oxford Forestry Institute, University of Oxford, 1988)
This is the eighth occasion on which research workers and practising foresters have met at the Oxford Forestry Institute to discuss ways of increasing the use of hardwoods in Britain. The presence of so many people from all sections of our industry indicates that interest continues undiminished. This year Peter Savill has joined with Rodney Helliwell in devising a joint programme which includes uneven-aged silviculture. There are three reasons why this is appropriate. The first is that the 1979-82 Census of Woodlands in England and Wales revealed that the area of broadleaved high forest has increased since the end of the last war. In particular, woodland made derelict by war time fellings has since been planted or become colonised by hardwoods, and other areas classed as scrub in the 1947 Census have since developed, either naturally or with management, into mixed broadleaved high forest. There are now several thousand hectares of woodland containing ash, birch, cherry and sycamore - in addition to beech and oak that could be converted into productive stands using systems of uneven-aged silviculture. The second reason why this joint programme is timely is the appearance of the report 'Beyond 2000' produced by the Forestry Industry Committee of Great Britain. This is the most optimistic appraisal of the forestry industry that I have read for a long time. After recounting the success of coniferous forestry in the uplands it lays particular stress on the need for a policy that will arrest the decline and ensure the expansion of broadleaved forestry, especially in the lowlands of Britain. The third reason derives from the objects of the National Hardwoods Programme and the Uneven-aged Silviculture Group. All foresters appreciate the beauty of hardwoods and recognise their importance in the landscape and in our wood-using industries. Re-reading many of the papers that have been presented at past meetings held here makes it clear that the knowledge and expertise required to make broadleaved high forest profitable as well as beautiful certainly does exist in Britain. We must make sure that the best examples of hardwood silviculture become more widely known and are available for study. Two systems of uneven-aged silviculture appear important for the future, namely, group selection and irregular shelterwood. These will be discussed today. I am sure that the Institute of Chartered Foresters and the two Royal Forestry Societies will continue to take an active interest in the development of these two systems in Britain, in addition to working with the Forestry Commission in formulating the policy for broadleaved forestry.